Pengaruh Keselamatan Kesehatan Kerja, Pelatihan dan Pengembangan Karir terhadap Kinerja Karyawan - Pandapotan Sitompul; Juniana P Guteres; Anitha Paulina Tinambunan; Kornel Munthe; Miska Irani Tarigan (SAFE-Network, 2023)
This research aims to determine the influence of occupational health safety, training and career development on employee performance. The research sample was taken using purposive sampling technique. The data collection method uses primary data by distributing questionnaires to respondents, namely PT employees. PLN (Persero) UP2B SUMBAGUT. The data collected is quantitative and will be analyzed using existing formulas assisted by SPSS version 26 software. The results of simultaneous hypothesis testing state that the variables of occupational health safety, training and career development simultaneously have a significant effect on the performance of PT employees. PLN (Persero) UP2B SUMBAGUT which can be seen from the significance value F < α, namely 0.000 < 0.05. The coefficient of determination of the Ajusted R Square value is 0.706, meaning that employee performance can be explained by the variables of occupational health safety, training and career development by 70.6%, while another 29.4% can be explained by other factors such as leadership, motivation, compensation and many more. which was not explained in this study.